PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN PAJAK, SANKSI PERPAJAKAN DAN KUALITAS PELAYANAN TERHADAP KEPATUHAN WAJIB PAJAK DI KANTOR PELAYANAN SAMSAT TALIWANG - Safitri, Novia (Jurnal Nusa Akuntansi, 2024)
This research aims to examine the influence of taxpayer awareness, tax knowledge, tax sanctions and service quality on taxpayer compliance in paying motor vehicle tax at the Samsat Taliwang office. This research uses a sampling technique with a purposive sampling method, namely using a population that has predetermined criteria to be used as a sample. The sample in this study numbered 97, namely tax payers in West Sumbawa Regency. The data analysis technique used in this research is multiple linear regression analysis using SPSS software. The results of this research show that Taxpayer awareness has a positive and significant effect on taxpayer compliance. Tax knowledge influences taxpayer compliance. Partial tax sanctions do not have a significant effect on taxpayer compliance. Partial service quality does not have a significant effect on taxpayer compliance. Based on the hypothesis test, taxpayer awareness and tax knowledge have a positive and significant effect on taxpayer compliance in paying motor vehicle taxes. Meanwhile, tax sanctions and partial service quality do not have a significant influence on taxpayer compliance.